The divining root: moisture-driven responses of roots at the micro- and macro-scale - Robbins, Neil E. (J Exp Bot, 2015)
Water is fundamental to plant life, but the mechanisms by which plant roots sense and respond to variations in water availability in the soil are poorly understood. Many studies of responses to water deficit have focused on large-scale effects of this stress, but have overlooked responses at the sub-organ or cellular level that give rise to emergent whole-plant phenotypes. We have recently discovered hydropatterning, an adaptive environmental response in which roots position new lateral branches according to the spatial distribution of available water across the circumferential axis. This discovery illustrates that roots are capable of sensing and responding to water availability at spatial scales far lower than those normally studied for such processes. This review will explore how roots respond to water availability with an emphasis on what is currently known at different spatial scales. Beginning at the micro-scale, there is a discussion of water physiology at the cellular level and proposed sensory mechanisms cells use to detect osmotic status. The implications of these principles are then explored in the context of cell and organ growth under non-stress and water-deficit conditions. Following this, several adaptive responses employed by roots to tailor their functionality to the local moisture environment are discussed, including patterning of lateral root development and generation of hydraulic barriers to limit water loss. We speculate that these micro-scale responses are necessary for optimal functionality of the root system in a heterogeneous moisture environment, allowing for efficient water uptake with minimal water loss during periods of drought.